Catches of the sport fishing competitions along the Algarve Coast (Portugal): species, sizes, catch rates, and trends - A.I. Guerreiro; P. Veiga; K. Erzini (Acta Ichthyologica et Piscatoria, 2011)
Background. Stocks of many marine fishes are in decline and a number of studies suggest that for some species the impact of recreational angling may be important. To date, only recreational (leisure) fishing surveys have been conducted in Portugal, with no studies on beach angling competitions, dynamically increasing in number over the past 10 to 20 years. In view of the above, we decided to evaluate the impact of such events on the Algarve coast (southern Portugal) in terms of the abundance, diversity, and respective weight of fish species caught and outline some conservation measures and recommendations for the management of the targeted species. Materials and methods. Participants of 22 angling competitions taking place between February and June 2007 were surveyed. In each competition a random sample of anglers was interviewed, and the specimens caught by each participant were identified, weighed, and measured. Results. Thirteen taxa belonging to eight families were identified, and the most common were: garfish, Belone belone (Linnaeus, 1761); mullets, Mugilidae (not identified); and mackerels, Scomber spp. A total of 563 specimens were sampled, totalling 75.4 kg of weight, with the average catch per angler weighing 0.5 ± 0.05 SE (n = 153) kg. Differences were also observed between the length at first maturity (L50) of the specimens caught and their respective Minimum Landing Size (MLS) and Allowed Minimum Size (AMS), most particularly in the case of the European seabass, Dicentrarchus labrax (L.), with almost all individuals caught measuring below the species-specific L50. Analysis of time series of competition results (1996–2009) showed no evidence of a decrease in catches or in mean weight. Conclusion. Based on the results we propose that the AMS for beach angling competitions should be increased to the MLS in order to prevent the capture of juvenile fishes, especially the sea bass. Future studies should address the size selectivity of the hooks used in beach competitions, with a view to the implementation of a minimum hook size for competitions.